In Situ Bioremediation of a Chlorinated Hydrocarbon Plume: A Superfund Site Field Pilot Test - Peter Guerra (MDPI AG, 2021)
The North Railroad Avenue Plume, discovered in 1989, contained chlorinated solvent groundwater plumes extending over 23.5 hectares (58 acres) and three hydrostratigraphic units. The source contaminant, tetrachloroethene, stemmed from release at a dry cleaner/laundromat business. The anaerobic biodegradation byproducts trichloroethene, isomers of dichloroethene (DCE), and vinyl chloride were detected in groundwater samples collected prior to remedial action. The impacted aquifers are the sole source drinking water aquifers for the communities near the site. Following the remedial investigation and feasibility study, the selected alternative for full-scale remedial action at the site was enhanced reductive dichlorination (ERD) focused on four treatment areas: the shallow source zone, the shallow hotspot area, the shallow downgradient area, and the deep zone. Pilot testing, which was conducted in the source zone and hotspot areas, is the subject of this paper. The primary objectives of the pilot test were to obtain the necessary information to select an ERD treatment formulation, dose, and frequency of dosing for use during full-scale remedial action, as well as to refine the site’s hydrogeologic conceptual site model and design parameters. Four (4) test cells, each of which contained well pairs of injection and downgradient extraction wells, were used to test ERD bio-amendment formulations: ethyl lactate, dairy whey, emulsified vegetable oil (EVO), and a combination of EVO and a hydrogen gas infusion. A conservative tracer, bromide, was added to the recirculation flow to record tracer breakthrough, peak, and dissipation at extraction wells. The results of these dipole tracer tests were used to reassess the hydraulic conductivity and hydrodynamic dispersity used in the remedial design. In addition to water quality analyses of contaminants and substrates, groundwater samples were also analyzed for biological analyses before, during, and after the addition of bioamendment. Analyses of phospholipid fatty acids and deoxyribonucleic acid (DNA) extracts from fresh groundwater samples informed decisions on the capacity for complete ERD without DCE stalling and tracked the shifts in the bacterial and archaeal taxonomy and phylogeny stemming from the addition of bioamendments. The pilot test concluded that EVO was the most suitable, considering (1) support of the native microbial consortia for ERD, (2) mechanics and hydraulics of the remediation system, and (3) sustainability/retention of the substrate in the subsurface. Along with EVO, the addition of a nutrient broth derived from brewery waste accelerated and sustained the desired conditions and microbial diversity and population levels. The pilot test results were also used to assess the utilization kinetics of the injected substrates based on total organic carbon (TOC) concentrations measured in the groundwater. After determining that substrate utilization followed Monod kinetics, a TOC threshold at 300 milligrams per liter, equivalent to approximately twice its half-saturation constant was established. Full scale treatment dosing and dose frequency were designed around this threshold, assuming the maximum substrate utilization would yield optimum ERD.